GENDER-SPECIFIC FINANCIAL DECISION MAKING: ANALYZING AWARENESS LEVELS AND INVESTMENT ATTITUDES AMONG WOMEN ENTREPRENEURS IN THOOTHUKUDI - Joescy, M. Maria Auxiliya; S. Vanitha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study examines the financial decision-making patterns, awareness levels, and investment attitudes among women entrepreneurs in Thoothukudi district, Tamil Nadu, India. Using a snowball sampling technique with 384 respondents, the research employs advanced statistical methods including cluster analysis and logistic regression to identify distinct entrepreneur profiles and predict financial behaviors. The cluster analysis reveals four distinct groups: Emerging Entrepreneurs (30.7%), Traditional Operators (37.0%), Growth-Oriented Leaders (23.2%), and Struggling Survivors (9.1%). Logistic regression models demonstrate that financial literacy, collateral availability, and family support are primary determinants of credit access, while business experience and education significantly influence investment attitudes. The study reveals critical gaps in financial literacy (average 48% score) and limited formal credit access (42.7%), despite widespread financing needs (73.4%). Key findings indicate that women entrepreneurs with higher financial sophistication achieve superior business outcomes, with Growth-Oriented Leaders showing 56.2% high growth rates compared to 8.6% among Struggling Survivors. The research contributes to understanding gender-specific financial behavior in entrepreneurial contexts and provides evidence-based recommendations for targeted interventions to enhance women's entrepreneurial success.